The Influence of Product Quality, Service Quality and WOM on Consumer Purchasing Decisions at Mie Ayam Goceng Setu Bekasi Food Stalls - Bagas mulyadi; Hadita (PT FORMOSA CENDEKIA GLOBAL, 2023)
There are many facts and data that state how big the influence of the culinary business in Indonesia is. It's not just a business related to basic human needs, more than that culinary business is entrepreneurial from an economic perspective. The purpose of this research is to study how product quality, service quality, and word of mouth influence consumers' decisions to buy goods. The research subjects were all restaurant consumers with a purposive sampling size of 100 respondents who ordered chicken noodles and ate on the spot. This research was analyzed using multiple linear regression. The results of this research state that the choice of product purchase is not influenced by its quality. On the other hand, service quality and word of mouth have a positive and significant effect on purchasing decisions. Additionally, product quality, service and consumer reputation influence buyers' decisions.